Holocene and Lateglacial relative sea‐level change in north‐west England: implications for glacial isostatic adjustment models. (25th September 2012) - Lloyd, Jeremy M.; Zong, Yongqiang; Fish, Paul; Innes, James B.
Abstract Relative sea‐level (RSL) change is reconstructed for central Cumbria, UK, based on litho‐ and biostratigraphical analysis from the Lateglacial to the late Holocene. The RSL curve is constrained using ten new radiocarbon‐dated sea‐level index points in addition to published data. The sea‐level curve identifies a clear Lateglacial sea‐level highstand approximately 2.3 m OD at c. 15–17 k cal a BP followed by rapid RSL fall to below −5 m OD. RSL then rose rapidly during the early Holocene culminating in a mid‐Holocene highstand of approximately 1 m OD at c. 6 k cal a BP followed by gradual fall to the present level. These new data provide an important test for the RSL predictions from glacial isostatic adjustment models, particularly for the Lateglacial where there are very little data from the UK. The new RSL curve shows similar broad‐scale trends in RSL movement predicted by the models. However, the more recent models fail to predict the Lateglacial sea level highstand above present reconstructed by the new data presented here. Future updates to the models are needed to reduce this mismatch. This study highlights the importance for further RSL data to constrain Lateglacial sea level from sites in northern Britain. Copyright © 2012 John Wiley & Sons, Ltd.